Pregnancy-related lumbopelvic pain – treatment modalities - Starzec Małgorzata; Truszczyńska Aleksandra (Advances in Rehabilitation, 2017)
Introduction: Pregnancy-related lumbopelvic pain is a common complaint which often limits everyday activity of a pregnant woman. Accurate and individualized treatment is needed as, if ignored, pain can become a long term condition. The aim of this article is to present the current state of knowledge about possible treatment modalities for pregnancy-related lumbopelvic pain.